EVALUATING THE ANTIFERTILITY POTENTIAL OF THE ETHANOLIC EXTRACTS OF BUPLEURUM SULPHUREUM AND CICHORIUM INTYBUS IN MALE RATS - TATLI-ÇANKAYA, IREM; Alqasoumi, Saleh I.; F. ABDEL-RAHMAN, REHAB; Yusufoglu, Hasan; Arabaci Anul, Serap; Akaydin, Galip; Soliman, Gamal A. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: In developing countries, population explosion is one of the most important causes of poverty and pollution. Therefore, several approaches have been investigated to decrease fertility, including hormonal, chemical and immunological approaches. However, no suitable method has been found to be effective and free from side effects. Thus, the aim of this study was to investigate the effect of B. sulphureum and C. intybus extracts on various parameters of male fertility using a rat model. Methods: Ethanolic extracts of both plants at doses of 125, 250 and 500 mg/kg, were each given orally to male Wistar rats for 7 weeks. Sperm characters and serum levels of sex hormones were assessed. Mating success percent, fertility success percent and fertility index were also calculated. The testes, liver and kidney were processed for histological examination. The effect on some biochemical and hematological parameters were quantified. Results:Â Results showed significant decrease in the weight of testes, epididymis, seminal vesicle and ventral prostate in the 250 and 500 mg/kg groups after 7 weeks of treatment. Both extracts reduced the motility, count and viability of sperms. Significant reduction in serum levels of testosterone, follicle-stimulating hormone (FSH) and luteinizing hormone (LH) with hyperprolactinemia were observed. Both extracts did not significantly alter any of the biochemical and hematologic parameters studied. Conclusion: These data suggest that administration of B. sulphureum and C. intybus extracts for 7 weeks contribute to reduce testicular and epididymal function in exposed rats. Keywords: B. sulphureum, C. intybus, mating trial, fertility index, testosterone, male fertility.